MOTIVASI DAN HASIL BELAJAR SISWA KELAS X PADA MATERI EKOSISTEM MELALUI PEMBELAJARAN BERBASIS MASALAH (PBL) - Mustika Piliang, Fenny; Rosenta Purba, Ika; Sinaga, Fiana (Jurnal Metabio, 2024)
This research aims to determine the effect of the project based learning model on student motivation and learning outcomes. in a pretest-posttest control group design. The research population was 75 students consisting of 2 classes at SMA Muhammadiah – 7 Serbelawan for the 2023/2024 academic year. The research sample was 75 students consisting of 2 classes, Student motivation is measured using a questionnaire while learning outcomes are measured using a multiple choice test. Next, the data obtained were analyzed using quantitative descriptive analysis by carrying out analytical prerequisite tests and hypothesis testing with a significance level of α = 0.05. The results of this research show that there is a significant influence in using the project based learning model on student learning motivation with a probability value of 0,05 (0,000 < 0,05) and tcount (0, 511) > ttable(1,666) and it can be concluded that Ha is accepted and H0 is rejected, which means there is a significant influence using a project based learning model on student learning outcomes with a probability value of 0,05 (0,000 < 0,05) and tcount 9,906 > ttable 3,122